Nucleic acid binding properties of the nucleic acid chaperone domain of hepatitis delta antigen - Wang, Chun-Chung (Nucleic Acids Res, 2003)
The N terminal region of hepatitis delta antigen (HDAg), referred to here as NdAg, has a nucleic acid chaperone activity that modulates the ribozyme activity of hepatitis delta virus (HDV) RNA and stimulates hammerhead ribozyme catalysis. We characterized the nucleic acid binding properties of NdAg, identified the structural and sequence domains important for nucleic acid binding, and studied the correlation between the nucleic acid binding ability and the nucleic acid chaperone activity. NdAg does not recognize the catalytic core of HDV ribozyme specifically. Instead, NdAg interacts with a variety of nucleic acids and has higher affinities to longer nucleic acids. The studies with RNA homopolymers reveal that the binding site size of NdAg is around nine nucleotides long. The extreme N terminal portion of NdAg, the following coiled-coil domain and the basic amino acid clusters in these regions are important for nucleic acid binding. The nucleic acid–NdAg complex is stabilized largely by electrostatic interactions. The formation of RNA–protein complex appears to be a prerequisite for facilitating hammerhead ribozyme catalysis of NdAg and its derivatives. Mutations that reduce the RNA binding activity or high ionic strength that destabilizes the RNA–protein complex, reduce the nucleic acid chaperone activity of NdAg.